A travessia do lúdico: modos de presença e regimes de interação dos games na cibercultura - Sousa, Juliana Pereira de (2014)
This research investigates the ways in which games are constituted as promoters of interactional mediation schemes of communication, sharing and production of meaning in the context of cyberculture. Identifies the potential of technological features of these digital environments, practices triggered by its use in contemporary society and proposals considered deflagrate aesthetic-cognitive experiences, beyond the field of entertainment and leisure, which we call the crossings. Guided by the problem posed in this scenario - "how (s) may mediate the games interactional regimes communication and production of meaning?" - Part of the research hypotheses that digital environments can be legitimized as a favoring practical experiences instituted by a rhetoric own aesthetic (and technological) qualities; and the possibility of displacement of these digital environments for other fields, such as ways to intuit sensitive cognitive-perception of individuals instituting regimes of interaction, in the act of communication events in different orders. Theorists clippings bounding rely on theories of media (like the aesthetics of communication) and in interdisciplinary studies of cyberculture, which also comprises the philosophy, through a rereading of authors said "classics" as Marshall McLuhan, Michael Foucault, Pierre Lévy, Immanuel Kant; contemporary authors like Lev Manovich, Ken Hillis, Henry Jenkins; sociodiscursive semiotics and of experience of Algirdas Greimas, Eric Landoswki, Jean-Marie Floch; among others. Brings, as empirical cut for in-depth research, beyond the realm of games, the game Minecraft (Mojanga AB), through ethnographic methodology and participant observation in the context of the game.